Communication Style and Cultural Adaptation of Nias Students in the City of Medan - Nurhasrat Laia; Humaizi; Amir Purba (Journal of Social Interactions and Humanities, 2023)
Tuti Halawa, a student from Nias who migrated to the city of Medan to continue her education at university. However, in interactions with the Medan community, Tuti experienced shock, she felt the Medan community's communication style was like someone angry. As a newcomer, Tuti comes to a new area that has a different language, culture, and tribe, she definitely feels a culture shock, but she is also required to adapt to that environment so that her interactions with the surrounding community are more comfortable. Based on this phenomenon, researchers are interested in analyzing the communication styles of Nias students in Medan. The purpose of this study was to analyze the communication style and cultural adaptation of Nias students in the city of Medan and identify the obstacles students experience in adapting. This study uses the theory of communication styles and cultural adaptation. This research was conducted with a qualitative approach and descriptive method. Data collection was carried out using interview and observation methods. The subjects in this study were determined using a purposive technique. The data analysis technique in this study uses the Miles and Huberman interaction model. The results obtained from this study found that Nias students experienced a change in communication style from a high-context communication style to a low-context communication style. In interaction with the Medan community, Nias students experience culture shock in the process of cultural adaptation. Overall, Nias students have managed to adapt well.